2013
DOI: 10.21836/pem20130501
|View full text |Cite
|
Sign up to set email alerts
|

Enrofloxacin concentrations in the vitreous of horses with equine recurrent uveitis (ERU) after repeated intravenous administration

Abstract: ZusammenfassungDie equine rezidivierende Uveitis (ERU) ist durch akut auftretende, rezidivierende serofibrinöse, gelegentlich auch durch serohaemorrhagische Entzündungen der Uvea und deren Folgen gekennzeichnet. Die Therapie des akuten Stadiums der Uveitis bestand und besteht in der konservativen Behandlung im Wesentlichen mit Mydriatika und Antiphlogistika. Rezidive konnten durch Entfernung des Glaskörpers und Spülung des Glaskörperraums (Vitrektomie) mit hoher Erfolgsrate verhindert werden. In an typischer E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Enrofloxacin after repeated intravenous dosing with 7.5 mg/kg bwt resulted in a peak concentration in aqueous humour of approximately 0.32 μg/mL while minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) for enrofloxacin against L. interrogans serovar Pomona strains in one report were 0.05–0.30 μg/mL . Although antibiotics such as enrofloxacin or some tetracyclines may reach concentrations above Leptospira MIC, they are mostly ineffective in eliminating the organism from the eye . Although there are no good data to show that systemic or topical antimicrobial use has been successful in eliminating Leptospira from the eye of horses with ERU, they could be effective in the rare case of uveitis associated with an acute infection .…”
Section: Treatmentmentioning
confidence: 99%
“…Enrofloxacin after repeated intravenous dosing with 7.5 mg/kg bwt resulted in a peak concentration in aqueous humour of approximately 0.32 μg/mL while minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) for enrofloxacin against L. interrogans serovar Pomona strains in one report were 0.05–0.30 μg/mL . Although antibiotics such as enrofloxacin or some tetracyclines may reach concentrations above Leptospira MIC, they are mostly ineffective in eliminating the organism from the eye . Although there are no good data to show that systemic or topical antimicrobial use has been successful in eliminating Leptospira from the eye of horses with ERU, they could be effective in the rare case of uveitis associated with an acute infection .…”
Section: Treatmentmentioning
confidence: 99%
“…Studies on autoimmune reactions, carried out by the research group of Deeg (Deeg et al 2001, Deeg et al 2002, Deeg et al 2004, Deeg et al 2006, Deeg 2008, were performed on identical intraocular samples from the same equine eyes used for the detection of an intraocular leptospiral infection mentioned above (Wollanke et al 1998a,b, Brem et al 1999a, Wollanke et al 2000b, Wollanke et al 2001a,b, Wollanke 2002, Hartskeerl et al 2004a, Niedermaier et al 2006, Brandes et al 2007, Roczek 2008, Loibl 2009, Wiehen 2012, Popp et al 2013, Roth et al 2014, Schinagl 2017.…”
Section: Introductionmentioning
confidence: 99%
“…; Popp et al . ). A recent study reported that systemic antibiotic therapy had minimal effect on visual outcome in horses with leptospirosis‐associated ERU as a positive titre may not indicate active infection but rather prior exposure (Gerding and Gilger ).…”
Section: Medical Therapymentioning
confidence: 97%